Resistance to glufosinate is proportional to phosphinothricin acetyltransferase expression and activity in LibertyLink (R) and WideStrike (R) cotton - Carbonari, Caio A. [UNESP]; Latorre, Debora O. [UNESP]; Gomes, Giovanna L. G. C. [UNESP]; Velini, Edivaldo D. [UNESP]; Owens, Daniel K.; Pan, Zhiqiang; Dayan, Franck E. (Springer, 2016)
Insertion of the gene encoding phosphinothricin acetyltransferase (PAT) has resulted in cotton plants resistant to the herbicide glufosinate. However, the lower expression and commensurate reduction in PAT activity is a key factor in the low level of injury observed in the WideStrike (A (R)) cotton and relatively high level of resistance observed in LibertyLink (A (R)) cotton. LibertyLink(A (R)) cotton cultivars are engineered for glufosinate resistance by overexpressing the bar gene that encodes phosphinothricin acetyltransferase (PAT), whereas the insect-resistant WideStrike(A (R)) cultivars were obtained using the similar pat gene as a selectable marker. The latter cultivars carry some level of resistance to glufosinate which enticed certain farmers to select this herbicide for weed control with WideStrike(A (R)) cotton. The potency of glufosinate on conventional FM 993, insect-resistant FM 975WS, and glufosinate-resistant IMACD 6001LL cotton cultivars was evaluated and contrasted to the relative levels of PAT expression and activity. Conventional cotton was sensitive to glufosinate. The single copy of the pat gene present in the insect-resistant cultivar resulted in very low RNA expression of the gene and undetectable PAT activity in in vitro assays. Nonetheless, the presence of this gene provided a good level of resistance to glufosinate in terms of visual injury and effect on photosynthetic electron transport. The injury is proportional to the amount of ammonia accumulation. The strong promoter associated with bar expression in the glufosinate-resistant cultivar led to high RNA expression levels and PAT activity which protected this cultivar from glufosinate injury. While the insect-resistant cultivar demonstrated a good level of resistance to glufosinate, its safety margin is lower than that of the glufosinate-resistant cultivar. Therefore, farmers should be extremely careful in using glufosinate on cultivars not expressly designed and commercialized as resistant to this herbicide.
Keywords: Ammonia; Glutamate; Photosynthesis; Marker gene; Pat; Bar; Injury; Gossypium hirsutum L; Glufosinate ammonium; Cotton